Scenarios for Ecodesign in loudspeaker’s motor - de Almeida, Allan Di Cunto D’Avila [UNESP]; Garde, Ivan Aritz Aldaya [UNESP]; dos Santos, Mirian Paula [UNESP]; Penchel, Rafael Abrantes [UNESP]; Filho, Lúcio Cardozo [UNESP]; de Oliveira, José Augusto [UNESP] (Springer Nature, 2022)
The worldwide loudspeaker market follows the growing tendency of electronic entertainment technologies both in quantity and variety. Consequently, the environmental impacts caused during the life cycle of loudspeakers increase in the same proportion, going in the opposite direction to what is determined by world environmental laws and regulations and global market tendencies. Even so, the environmental performance of this type of product is not considered in the decision-making process for technological updates in loudspeaker design. In this sense, Ecodesign is the most adequate Life Cycle Engineering tool applied in the design of a product since the environmental performance is considered throughout the different design stages. However, the feasibility of Ecodesign in products requiring complex production chains relies on splitting the product into subsystems and components. Thus, the present work focuses on evaluating the environmental performance of a classic loudspeaker motor, which is composed of a magnet, coil, and coil former. Eight raw material substitution scenarios are proposed and analyzed, which allowed the proposal identification with the best environmental performance within the current technologies. This represents an initial step toward the complete Ecodesign of a loudspeaker and sets the procedure to be followed with the other constitutive parts.